2022
DOI: 10.1039/d2nr00444e
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable, breathable, and highly sensitive capacitive and self-powered electronic skin based on core–shell nanofibers

Abstract: Fiber-based nanostructures are greatly desired for the improvement of wearable/flexible electronics which are stretchable, conformable, flexible, long-term. Herein, an ultra-stretchable, breathable, and high sensitive flexible capacitive tactile sensor and triboelectric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Here, we suggested a versatile technique to assemble an ultrahighly stretchable yarn that consists of the TPU yarn, LM deposited to the surface of the TPU yarn, and nanofibers as the protective layer of the LM by simple electrospinning. It was found in our previous studies that liquid metal can be fully patterned onto a TPU nanofiber film. , The obtained TPU/LM/NFs yarn has shown an excellent large strain range (≈548%) and a high strength (≈40 MPa). The TPU/LM/NFs yarn could be utilized as highly stretchable and deformable conductors to charge a mobile phone or for data transfer.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Here, we suggested a versatile technique to assemble an ultrahighly stretchable yarn that consists of the TPU yarn, LM deposited to the surface of the TPU yarn, and nanofibers as the protective layer of the LM by simple electrospinning. It was found in our previous studies that liquid metal can be fully patterned onto a TPU nanofiber film. , The obtained TPU/LM/NFs yarn has shown an excellent large strain range (≈548%) and a high strength (≈40 MPa). The TPU/LM/NFs yarn could be utilized as highly stretchable and deformable conductors to charge a mobile phone or for data transfer.…”
Section: Introductionmentioning
confidence: 75%
“…Second, the LM was printed on the obtained stretchable nanoyarn; based on our previous study, it was confirmed that the LM can well adhere to the TPU surface. 31,34,35 Figure 1a(ii) shows the LM successfully printed on the TPU nanoyarn. Finally, TPU/LM was covered by TPU nanofibers not only to protect the LM but also to strengthen it, which was adhered to the layer of the LM/TPU by making a thin layer of TPU/LM/NFs as shown in Figure 1a(iii).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the aforementioned, other hierarchal structures have also been adopted for triboelectric materials, which fall into three main categories: beaded fibers, [51] hollow fibers, [54] and special 3D structures. [65,170] Beaded fibers are hierarchical fibers between microparticles and fibers. This hierarchical structure increases the surface area and surface roughness of materials, which has considerable potential for applications in high-performance and waterproof self-powered TENGs.…”
Section: Characteristics and Properties Of Hierarchically Structured ...mentioning
confidence: 99%
“…96,97 Core−shell TPU/ILs/PVDF-HFP nanofibers were prepared by coaxial electrospinning with the core solution of TPU and I L s ( 1 -e t h y l -3 -m e t h y l i m i d a z o l i u m b i s - (trifluoromethylsulfonyl)imide) and the shell solution of PVDF-HFP. 98 The flexible capacitive sensor fabricated by the core−shell fibers had a high sensitivity (0.718 kPa −1 ), an ultralow detection limit (7 Pa), and a good stability under a low linear pressure range (0−1.2 kPa). However, the skin compliance and permeability of the capacitance sensor based on ILs mentioned above are limited.…”
mentioning
confidence: 99%